Sestrin-2, a repressor of PDGFRβ signalling, promotes cigarette-smoke-induced pulmonary emphysema in mice and is upregulated in individuals with COPD - Juliana Heidler; Athanasios Fysikopoulos; Frank Wempe; Michael Seimetz; Thorsten Bangsow; Ana Tomasovic; Florian Veit; Susan Scheibe; Alexandra Pichl; Friederike Weisel; K. C. Kent Lloyd; Peter Jaksch; et al. (The Company of Biologists, 2013)
SUMMARY Chronic obstructive pulmonary disease (COPD) is a leading cause of morbidity and mortality worldwide. COPD is caused by chronic exposure to cigarette smoke and/or other environmental pollutants that are believed to induce reactive oxygen species (ROS) that gradually disrupt signalling pathways responsible for maintaining lung integrity. Here we identify the antioxidant protein sestrin-2 (SESN2) as a repressor of PDGFRβ signalling, and PDGFRβ signalling as an upstream regulator of alveolar maintenance programmes. In mice, the mutational inactivation of Sesn2 prevents the development of cigarette-smoke-induced pulmonary emphysema by upregulating PDGFRβ expression via a selective accumulation of intracellular superoxide anions (O2−). We also show that SESN2 is overexpressed and PDGFRβ downregulated in the emphysematous lungs of individuals with COPD and to a lesser extent in human lungs of habitual smokers without COPD, implicating a negative SESN2-PDGFRβ interrelationship in the pathogenesis of COPD. Taken together, our results imply that SESN2 could serve as both a biomarker and as a drug target in the clinical management of COPD.